QUANTIFICATION OF THE AMOUNT OF UNJUST ENRICHMENT IN RELATION TO SALE OF A PLOT OF LAND BUILT UP WITH A STRUCTURE OF ANOTHER OWNER - Klišová, Jana; Studnařová, Martina (European Scientific Journal, ESJ, 2014)
The article is a short essay describing the previous and current situation in the legal regulation of the Czech Republic governing the two specific areas of evaluation referred to in the title: - amount of unjust enrichment, and - normal price of a plot of land built up with a structure of another owner. The article’s aim is to make the professional public familiar with and inform it about the legislation gaps existing in the Czech Republic, which are not only negatively reflected in the valuation practice, but also affect the general public. The topic of this article resulted from processing the issue of dissertations of the authors.